Classification of segmental vitiligo on the trunk. (1st February 2014) - van Geel, N.; Bosma, S.; Boone, B.; Speeckaert, R.
Summary: Background: Segmental vitiligo is characterized by a unilateral and localized distribution. A classification for segmental vitiligo on the face has been proposed, while this is still unavailable for lesions on the trunk. Objectives: To design a classification for segmental vitiligo lesions on the trunk by evaluating their distribution pattern. Methods: In this retrospective observational study, the distribution pattern of 106 segmental vitiligo lesions on the trunk was analysed and classified into recurring subtypes. Results: Segmental vitiligo was more frequently observed on the ventral side (85·8%) than the lateral side (52·8%) or the back (36·8%) of the trunk. Based on recurring similarities in distribution patterns, lesions were categorized into six distinct subtypes: types 1, 2 and 3 involved the upper part of the trunk, type 4 and 5 the middle part and type 6 the lower part of the trunk. In total, 67·9% of all segmental vitiligo lesions fitted into these subtypes. The most frequent type of lesion was subtype 3 (22·6%), which showed a characteristic V‐shaped pattern on the upper trunk, followed by subtype 5 (17·9%), with a band‐like pattern on the lateral side, and subtype 6 (13·2%), with a rectangular depigmentation on the lower abdomen. Conclusions: Based on our observations we suggest a new classification into six subtypes for segmental vitiligo lesions on the trunk, allowing categorization of the majority of segmental vitiligo patterns on the trunk. This may have important prognostic and diagnostic significance in early developing lesions.